KARAKALPAK THEATER DIRECTOR (On the example of puppet theatre director M. Begimov) (ART AND CULTURE BULLETIN, 2026)
This article tells about the life and work of director Murat Begimov, who worked selflessly at the Karakalpak puppet theater for several years.
Keywords: theatre; director; puppet; play; actor